Global evaluation and sensitivity analysis of a physically based flow and reactive transport model on a laboratory experiment. (March 2019) - Gatel, Laura; Lauvernet, Claire; Carluer, Nadia; Weill, Sylvain; Tournebize, Julien; Paniconi, Claudio
Abstract: Spatialized physically based models are necessary tools for assessing the fate of pesticides in natural environments transferred by diffuse pollution. In this study the CATHY (CATchment HYdrology) model is coupled with reactive processes (adsorption and degradation). The resulting reactive subsurface component is evaluated on laboratory data by (i) comparing the model performance on experimental data using a combination of statistical criteria, (ii) conducting a Morris sensitivity analysis on both hydrological and solute transfer variables, and (iii) improving the CATHY model parameter settings based on the sensitivity analysis results. The sensitivity analysis produces a ranking of the factors wherein those that are particularly influential on water flow and reactive solute transfer emerge. These are found to be the saturated hydraulic conductivity, the retention curve parameters, and the sorption coefficient. After a calibration of influential parameters based on Morris sensitivity analysis, the results obtained are largely consistent with laboratory data. Highlights: The surface-subsurface model CATHY was extended to include reactive transport. The model is able to reproduce a tracer and pesticide laboratory experiment. Pesticide fluxes are primarily influenced by conductivity, porosity, and K O C . Calibration subsequent to Morris sensitivity analysis improves model performance.